Redesigning the college library building, 2014 edition (Primary Research Group, 2014)
This report looks closely at college plans to restructure or alter space use in college libraries. The 190+ page study gives detailed data on college library plans to increase or decrease space for various departments and purposes, how they plan to develop and deploy their capital budgets, which types of projects and purposes are favored for the near future. The report helps librarians to answer questions such as: How many workstations will libraries deploy? Will the number increase or decrease? What about space allocated to information commons? Or to classroom space? What about office space? Collection space? Space for special collections? The report helps its end users to stay on the cutting edge, to find out what library planners are hoping to achieve in the near future. The study also looks at budgets for repairs, and for major renovations and gives data for overall budgets and on a per student enrolled basis. Data in the study is broken out by size and type of college, with separate data for community colleges, research universities, 4-year colleges and those non-research universities that grant MA/PhD degrees